Effects of Lipophilicity and Structural Features on the Antiherpes Activity of Digitalis Cardenolides and Derivatives. Issue 10 (29th September 2022) - de Pádua, Rodrigo Maia; Kratz, Jadel Müller; Munkert, Jennifer; Bertol, Jéssica Wildgrube; Rigotto, Caroline; Schuster, Daniela; Maltarollo, Vinícius Gonçalves; Kreis, Wolfgang; Simões, Cláudia Maria Oliveira; Braga, Fernão Castro
Abstract: There is growing interest in exploring Digitalis cardenolides as potential antiviral agents. Hence, we herein investigated the influence of structural features and lipophilicity on the antiherpes activity of 65 natural and semisynthetic cardenolides assayed in vitro against HSV‐1. The presence of an α, β‐unsaturated lactone ring at C‐17, a β‐hydroxy group at C‐14 and C‐3β‐OR substituents were considered essential requirements for this biological activity. Glycosides were more active than their genins, especially monoglycosides containing a rhamnose residue. The activity enhanced in derivatives bearing an aldehyde group at C‐19 instead of a methyl group, whereas inserting a C‐5β‐OH improved the antiherpes effect significantly. The cardenolides lipophilicity was accessed by measuring experimentally their log P values ( n ‐octanol‐water partition coefficient) and disclosed a range of lipophilicity (log P 0.75±0.25) associated with the optimal antiherpes activity. In silico studies were carried out and resulted in the establishment of two predictive models potentially useful to identify and/or optimize novel antiherpes cardenolides. The effectiveness of the models was confirmed by retrospective analysis of the studied compounds. This is the first SAR study addressing the antiherpes activity of cardenolides. The developed computational models were able to predict the active cardenolides and their log P values. Abstract :